Synthesis, antibacterial, and antioxidant studies of 7-amino-3-(4-fluorobenzoyl)indolizine-1-carboxylate derivatives - Vijayakumar Uppar, Sandeep Chandrashekharappa, Atiyaparveen I. Basarikatti, Govindappa Banuprakash, Mahendra K. Mohan, Mallikarjun Chougala, Kiran K. Mudnakudu-Nagaraju, Raghu Ningegowda, Basavaraj Padmashali (Journal of Applied Pharmaceutical Science, 2020)
In the present work, the quaternary salts of 4-aminopyridine, i.e., 4-amino-1-[2-(4-bromophenyl)-2-oxoethyl]pyridin-1-ium bromides were obtained by stirring 4-aminopyridine with phenacyl bromides in acetone at room temperature separately. These quaternary salts of 4-aminopyridine were treated with acetylenes (electron deficient), in the presence of anhydrous possium carbonate in N,N-dimethylformamide solvent to get indolizine derivatives. The structures of newly synthesised compounds have been confirmed by spectroscopic techniques, such as liquid chromatography mass spectrometry, 1H-NMR, and elemental analysis. Synthesized all compounds were screened for antibacterial and antioxidant activity. The compounds 2e, 2g, and 2j shows inhibition zone against bacteria and compounds 2a and 2f moderately active against bacteria. All compounds 2a to 2j show 1,1-diphenyl-2-picrylhydrazide radical free radical scavenging activity, Nitric Oxide free radical scavenging activity, Reducing power scavenging activity, and Lipid peroxidation inhibition activity.
Keywords: Indolizine, 4-aminopyridine, acetylene, anti-bacterial, antioxidant.